V.1 - Waldrep, Christopher (New York, 2003)
The United States Constitution records the structure of America$1 (Bs public life and society, distributing power and outlining citizens$1 (Brights and privileges. Historians Christopher Waldrep and Lynne Curry$1 (Bs compilation of leading interpretive documents traces English and American constitutional thinking from its earliest roots in 1215, to the U.S. Supreme Court under the great chief justice John Marshall. These documents reveal the constitution as an idea, growing and evolving but always reflecting particular moments in history. This book records the drama of the young American nation searching for its identity.s
Keywords: Constitutional history-United stated